(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
This article examines the preventive potential of physical activity in reducing occupational diseases among employees of oil and gas enterprises. The relevance of the topic is determined by the specific working conditions of the industry, including prolonged static loads, shift-based labor organization, exposure to adverse climatic and industrial factors, psycho-emotional tension, and limited opportunities for maintaining a healthy lifestyle during work periods. Under such conditions, employees are at increased risk of musculoskeletal disorders, cardiovascular dysfunctions, metabolic disturbances, chronic fatigue, and stress-related conditions. The study focuses on the role of systematic physical activity as an effective means of preserving working capacity, strengthening adaptive mechanisms, and improving the overall functional state of the body. It is argued that regular exercise, production gymnastics, corrective motor programs, and corporate wellness initiatives can significantly reduce the incidence of occupationally conditioned disorders and improve health indicators in the workforce. Special attention is given to the integration of preventive physical culture into occupational health systems at oil and gas enterprises, as well as to the need for differentiated approaches based on age, workload, work environment, and medical status. The article substantiates that physical activity should be considered not only as a general health factor but also as an important organizational and pedagogical tool for strengthening labor safety and reducing occupational health risks in the oil and gas sector.